Deuterated Molecular Ruby with Record Luminescence Quantum Yield. Issue 4 (2nd January 2018) - Wang, Cui; Otto, Sven; Dorn, Matthias; Kreidt, Elisabeth; Lebon, Jakob; Sršan, Laura; Di Martino‐Fumo, Patrick; Gerhards, Markus; Resch‐Genger, Ute; Seitz, Michael; Heinze, Katja
Abstract: The recently reported luminescent chromium(III) complex1 3+ ([Cr(ddpd)2 ] 3+ ; ddpd= N, N ′‐dimethyl‐ N, N ′‐dipyridine‐2‐yl‐pyridine‐2, 6‐diamine) shows exceptionally strong near‐IR emission at 775 nm in water under ambient conditions ( Φ =11 %) with a microsecond lifetime as the ligand design in1 3+ effectively eliminates non‐radiative decay pathways, such as photosubstitution, back‐intersystem crossing, and trigonal twists. In the absence of energy acceptors, such as dioxygen, the remaining decay pathways are energy transfer to high energy solvent and ligand oscillators, namely OH and CH stretching vibrations. Selective deuteration of the solvents and the ddpd ligands probes the efficiency of these oscillators in the excited state deactivation. Addressing these energy‐transfer pathways in the first and second coordination sphere furnishes a record 30 % quantum yield and a 2.3 millisecond lifetime for a metal complex with an earth‐abundant metal ion in solution at room temperature. Abstract : Record ruby : Deuteration of the solvent and especially the ligand boosts the photoluminescence quantum yield of the chromium(III) complex with strong‐field ddpd ligands (molecular ruby) from 11 % to a record value of 30 % in solution at room temperature. At the same time, the luminescence lifetime more than doubles to over two milliseconds. The α‐CH group of the ddpd ligand provides the most decisive oscillator.